2020
DOI: 10.3390/ijerph17041429
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Differences Between Deliberate Self-Harm with and without Suicidal Intent Amongst a Clinical Sample of Young People in Singapore: A Cross-Sectional Study

Abstract: This study examined differences between young people with mental illness who engage in deliberate self-harm with and without suicidal intent, as well as socio-demographic and clinical factors that are related to the increased likelihood of suicide attempt amongst self-harming young people. A total of 235 outpatients with mental illness who had engaged in deliberate self-harm were recruited from a tertiary psychiatric hospital in Singapore. Participants completed a self-report questionnaire which collected info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…According to our initial hypothesis, the diversity of DSH behaviors was a predictor of SI and SAs, which remained significant when controlling for the effect of DSH severity. These results are similar to those found in previous studies (Hamza and Willoughby, 2013;Samari et al, 2020;Wester et al, 2016). However, in our study, diversity was a stronger predictor of SAs than in the study of Duarte and colleagues (2020), which highlights the importance of DSH diversity both for clinical and research settings.…”
Section: Dsh Diversity and Severity As Predictors Of Si And Sasupporting
confidence: 92%
See 2 more Smart Citations
“…According to our initial hypothesis, the diversity of DSH behaviors was a predictor of SI and SAs, which remained significant when controlling for the effect of DSH severity. These results are similar to those found in previous studies (Hamza and Willoughby, 2013;Samari et al, 2020;Wester et al, 2016). However, in our study, diversity was a stronger predictor of SAs than in the study of Duarte and colleagues (2020), which highlights the importance of DSH diversity both for clinical and research settings.…”
Section: Dsh Diversity and Severity As Predictors Of Si And Sasupporting
confidence: 92%
“…Thus, in the current study, we have two main goals: a) to characterize DSH diversity and severity, SI and SAs, and how these variables relate in a clinical and community sample of Portuguese adolescents with a history of DSH; and b) to analyze how impactful is the diversity and severity of DSH on SI and SAs. Since previous research has concluded that DSH diversity is associated with SI and SAs, we hypothesize that DSH diversity will predict SI and SAs (Duarte et al, 2020;Hamza and Willoughby, 2013;Samari et al, 2020;Wester et al, 2016). There is also evidence that individuals who have SAs engage in more severe DSH (Stewart et al, 2017).…”
Section: The Current Studymentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, only a handful of longitudinal studies have assessed the association between cannabis use and suicide death with mixed findings 1,3–6 . In addition to suicidal behavior‐related outcomes, “self‐harm” and “deliberate self‐harm” defined as intentional self‐injurious behavior regardless of preceding objective have been examined in previous research 3,7,8 . A recent meta‐analysis of nine cohort studies by Escelsior et al reported an association between cannabis use and self‐injurious behavior 9 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 3 , 4 , 5 , 6 In addition to suicidal behavior‐related outcomes, “self‐harm” and “deliberate self‐harm” defined as intentional self‐injurious behavior regardless of preceding objective have been examined in previous research. 3 , 7 , 8 A recent meta‐analysis of nine cohort studies by Escelsior et al reported an association between cannabis use and self‐injurious behavior. 9 Yet, significant knowledge gaps remain in our understanding of the association between specifically adolescent cannabis use and subsequent intentional self‐injury‐related outcomes.…”
Section: Introductionmentioning
confidence: 99%